2022
DOI: 10.3390/jcm11247510
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Associated Differences in Short-Term Outcomes in Patients with Deep Sternal Wound Infection after Open-Heart Surgery

Abstract: Deep sternal wound infection (DSWI) is a feared complication after cardiac surgery. The impact of sex-related differences on wound infection prevalence is poorly understood. Our aim was to evaluate the effect of sex on short-term outcomes in patients with DSWI after open-heart surgery. The study was a retrospective cohort study. A total of 217 patients with DSWI were identified and retrospectively analyzed using our institutional database. Patients were divided into two groups: males (n = 150) and females (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…Biancari et al found that the female sex is a predictor for the development of deep sternal wound infections [ 14 ]. Breyer et al and Itagaki et al also demonstrated a significantly higher occurrence of postoperative deep sternal wound infections in women and concluded that the female sex is an independent risk factor for the development of deep sternal wound infections, whereas Krasivskyi et al, in their study, did not see such a difference [ 30 , 31 , 32 ]. Gatti et al analyzed 2.872 patients after isolated CABG surgery and showed that the female sex was a strong predictor of DSWI [ 33 ].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Biancari et al found that the female sex is a predictor for the development of deep sternal wound infections [ 14 ]. Breyer et al and Itagaki et al also demonstrated a significantly higher occurrence of postoperative deep sternal wound infections in women and concluded that the female sex is an independent risk factor for the development of deep sternal wound infections, whereas Krasivskyi et al, in their study, did not see such a difference [ 30 , 31 , 32 ]. Gatti et al analyzed 2.872 patients after isolated CABG surgery and showed that the female sex was a strong predictor of DSWI [ 33 ].…”
Section: Discussionmentioning
confidence: 93%
“…The interaction between CABG and one or both ITAs, along with female sex, were strongly associated with CDC-negative surgical site infection (SSI). Indeed, tension of the breast upon the skin wound may be an additional risk factor for delayed wound healing and wound leakage, leading to SSI [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…We formed two groups to investigate potential sex-related differences in early clinical outcomes: men (n = 255) and women (n = 88). To account for the unequal cohort sizes, we performed a propensity score-based matching (PSM) analysis using the methods previously described [ 22 ]. The details of the analysis are provided in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Standard anticoagulation protocols were used by all patients after the OPCAB procedure, which were similar in Cologne and Tuebingen. Our methods were previously described [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Існують різні думки щодо впливу статі на інфекційні ускладнення у ділянці грудини після операції. Деякі дослідження показали відсутність впливу статі на поширеність глибокої стернальної ранової інфекції після кардіохірургічного втручання [9]. У нашій вибірці більшість були чоловіками -10 (83,3 %).…”
unclassified